Crop diversification in Bangladesh: Public policy provisions, practices, and insights for future initiatives - Nandi, Ravi; Krupnik, Timothy J.; Kabir, Wais (Elsevier, 2024)
Bangladesh's agriculture and diet are highly rice-centric, although rational, risky, and arguably unsustainable. This necessitates a focus on crop diversification to enhance food security, build resilience, and promote environmental sustainability. This study provides a comprehensive analysis of crop diversification policy provisions, programs, projects, and trends in Bangladesh from 1971 to 2023, highlighting their evolution, implementation, and impacts. The objective is to inform future policy and operational decisions to enhance the effectiveness of crop diversification efforts. An integrated analytical framework is utilized, incorporating a review of historical agriculture policies, Five-Year Plans (FYPs), and 1223 project reports. The study employed the Herfindahl-Hirschman Index (HHI) to quantify crop diversification and conducted Key Informant Interviews (KIIs) with stakeholders using a snowball sampling method. The analysis identified eight FYPs, 12 specific policies, and 81 projects, with 19 explicitly focusing on crop diversification. Despite significant policy support, implementation has faced challenges due to historical policy biases, insufficient funding, and market and project implementation challenges. The study reveals that despite numerous initiatives, crop diversification remains low, with a need for better infrastructure, market linkages, and incentives for farmers. To achieve sustainable agricultural growth, the Government of Bangladesh should mainstream crop diversification through annual budgets, enhance institutional capacities, and foster public-private partnerships, alongside strengthening the effective implementation of projects. This research provides valuable insights and practical guidelines for policymakers and development practitioners to promote sustainable agriculture in Bangladesh through specific policy and operational initiatives.